Roles of the MYB94/FUSED LEAVES1 (ZmFDL1) and GLOSSY2 (ZmGL2) genes in cuticle biosynthesis and potential impacts on Fusarium verticillioides growth on maize silks - Castorina, Giulia; Bigelow, Madison; Hattery, Travis; Zilio, Massimo; Sangiorgio, Stefano; Caporali, Elisabetta; Venturini, Giovanni; Iriti, Marcello; Yandeau-Nelson, Marna D.; Consonni, Gabriella (Frontiers in Plant Science, 2023)
Maize silks, the stigmatic portions of the female flowers, have an important role in reproductive development. Silks also provide entry points for pathogens into host tissues since fungal hyphae move along the surface of the silks to reach the site of infection, i.e., the developing kernel. The outer extracellular surface of the silk is covered by a protective hydrophobic cuticle, comprised of a complex array of long-chain hydrocarbons and small amounts of very long chain fatty acids and fatty alcohols. This work illustrates that two previously characterized cuticle-related genes separately exert roles on maize silk cuticle deposition and function. ZmMYB94/FUSED LEAVES 1 (ZmFDL1) MYB transcription factor is a key regulator of cuticle deposition in maize seedlings. The ZmGLOSSY2 (ZmGL2) gene, a putative member of the BAHD superfamily of acyltransferases with close sequence similarity to the Arabidopsis AtCER2 gene, is involved in the elongation of the fatty acid chains that serve as precursors of the waxes on young leaves. In silks, lack of ZmFDL1 action generates a decrease ha eliminato: Giulia